A method for hydriding, crushing and powdering large-size valve metal ingots
By using ultra-high-purity hydrogen with a dew point below -70℃ for hydrogenation, the problem of difficulty in thorough hydrogenation of large-scale valve metal ingots is solved, efficient and low-cost powder production is achieved, and the performance and safety of the powder are optimized.
Patent Information
- Application Number
- CN202110239762.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-04
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-03-04
AI Technical Summary
The prior art is difficult to handle large-scale valve metal ingots for thorough hydrogenation, resulting in cumbersome process, high cost and inability to effectively control the particle size distribution of the powder, resulting in the generation of ultrafine powder.
Ultra-high-purity hydrogen gas with a dew point below -70℃ is used for hydrogenation treatment. By controlling the hydrogenation conditions and hydrogen content, a large-scale valve metal ingot is fully hydrogenated at one time, and powder is obtained by crushing and powder making.
The complete hydrogenation of large-scale valve metal ingots has been achieved, which reduces production costs, optimizes the particle size distribution and performance of the powder, and avoids the safety risk of hydrogen leakage.
Smart Images

Figure BDA0002961663940000091 
Figure BDA0002961663940000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of powder production by hydrogenation of valve metal ingots, and more specifically to a preparation method for producing metal powder by moderately hydrogenating large-sized valve metal and alloy ingots thereof and then crushing and powdering them. Background Art
[0002] Valve metal hydride crushing and powdering is the most common means of producing corresponding metal powders, especially in the production of metal powders with low oxygen content, high component purity and strict particle size distribution requirements. With the continuous application of new processing technologies for valve metals and their alloys, such as spray deposition, metal injection molding, laser rapid prototyping, 3D printing technology, or use as alloy additives, valve metal powders have strict requirements not only in terms of oxygen content and component purity, but also in terms of particle size distribution. Not only are the particle size requirements high, but also a relatively narrow particle size distribution is required; on the other hand, in the production of valve metal powders, reducing production costs and improving production efficiency are of great significance. As a rare metal, the raw material cost of valve metal accounts for the highest proportion of the total production cost, reaching more than 70%, or even more than 80%. Therefore, reducing the unit consumption of raw materials in production will effectively reduce production costs. If the particle size distribution of valve metal powder after hydride crushing can be consistent with or closer to the particle size distribution required by the product, the production cost will be greatly reduced.
[0003] The Chinese patent application "Tantalum and / or niobium powder for powder metallurgy and its preparation method" (application number CN201310636343.2) provides a process for hydrogenating and powdering tantalum and / or niobium waste sintered blocks, firstly destroying the surface oxide layer of the tantalum and / or niobium sintered blocks, then using high-purity hydrogen for hydrogenation, and then crushing and powdering.
[0004] In the existing valve metal hydrogenation crushing and powder making technology, the destruction of the metal surface oxide layer during the hydrogenation process, the purity of the hydrogen used, the cooling and hydrogen absorption conditions, etc. have been studied. However, the existing technology cannot process large-scale valve metal ingots. Most of the valve metals are in the form of sponges or turnings, and the single processing volume is very small. Even if metal ingots are used for processing, the ingots are very small, usually only a few dozen kilograms at most. More importantly, the existing technology cannot solve the problem of one-time thorough hydrogenation when hydrogenating large-scale valve metal alloy ingots, that is, it has failed to break through the technical bottleneck of automatic hydrogenation stopping in the middle of hydrogenation; therefore, repeated hydrogenation is often required, and the process is cumbersome. Moreover, the existing technology cannot effectively control the particle size distribution of valve metal powder produced by the hydrogenation crushing and powder making process, which increases the unit consumption of the valve metal powder production process. The above technical defects increase the production cost of valve metal powder. At the same time, the presence of ultrafine powder deteriorates the performance of valve metal powder, such as the increase in oxygen content.
[0005] The inventors have discovered that an important reason why large-sized valve metal ingots cannot be hydrogenated thoroughly in one go using the existing technology is that the valve metal has a secondary surface passivation problem during the hydrogenation process. If secondary passivation occurs, the hydrogenation stops, resulting in insufficient hydrogen absorption of some valve metals, poor hydrogen embrittlement, and inability to crush and powder.
[0006] Another problem with the prior art is that the over-hydrogenated valve metal block may leak hydrogen during storage, causing safety accidents.
[0007] In summary, the prior art has always wanted to use large-sized ingots as raw materials, which can greatly improve production efficiency and effectively reduce costs from multiple processes such as valve metal ingot smelting and hydrogenation. However, before the present invention, it was unable to solve the problem of completely hydrogenating large-sized ingots at one time. Summary of the invention
[0008] The present invention provides a method for preparing powder by hydrogenation crushing of valve metal. Those skilled in the art know the specific meaning of valve metal. In this article, the meaning of valve metal is as known in the art, for example, including tantalum, niobium, tantalum alloy, niobium alloy and tantalum-niobium alloy, etc. The present invention is particularly illustrated by tantalum and niobium.
[0009] One object of the present invention is to provide a method for preparing powder by using large-sized valve metal ingots as raw materials. In particular, "large size" means that the mass of the metal ingot is more than 100 kg, such as more than 200 kg, more than 300 kg, or even more than 400 kg, preferably more than 500 kg, more preferably more than 600 kg, such as more than 700 kg, more than 800 kg. There is no particular restriction on the upper limit of the mass of the ingot, as long as the actual process conditions allow. However, considering the current production conditions, in order to avoid the trouble of modifying the production line and reduce the production safety risks, the weight of the ingot is preferably less than 1200 kg, more preferably less than 1100 kg, and more preferably less than 1000 kg.
[0010] Another purpose of the present invention is to solve the secondary passivation problem in the valve metal hydrogenation process. After a large number of experiments, the inventor unexpectedly found that the use of ultra-high purity hydrogen with a dew point below -70°C can effectively solve the secondary passivation problem and achieve a one-time complete hydrogenation of large-sized valve metal ingots. The dew point is an important indicator of the purity of the reaction hydrogen. The higher the water content in the hydrogen, the higher the dew point. The inventor found that the higher the dew point, the more likely the water content in the hydrogen will cause secondary passivation problems on the metal surface.
[0011] Another object of the present invention is to obtain a valve metal with a hydrogen content within an optimized range. For example, when the valve metal is niobium, it is advantageous to produce niobium with a hydrogen content of 0.8-1.3%, preferably 0.9-1.2%, and more preferably 0.95-1.1%. When the valve metal is tantalum, it is advantageous to produce tantalum with a hydrogen content of 0.3-0.5%, preferably 0.35-0.45%. When a valve metal with an optimal hydrogen content is used to crush and pulverize the corresponding metal powder, the hydrogenated block of the valve metal can maintain good hydrogen embrittlement, and the particle size distribution of the crushing and pulverizing process can be narrowed, reducing the generation of ultrafine powder, thereby reducing the unit consumption of valve metal powder production, and optimizing the comprehensive performance of the product. As is well known to those skilled in the art, the presence of ultrafine powder (especially -500 mesh ultrafine powder) will lead to the shortcomings of poor fluidity, low spray deposition rate, and high oxygen content of valve metal powder. Therefore, preferably, when the valve metal block is crushed to less than 100 mesh by the present invention, the -500 mesh powder of the obtained valve metal powder is less than 20% (, preferably less than 15%, more preferably less than 10%, even more preferably less than 8%, and most preferably less than 6%.
[0012] However, in some cases, there may be a need for ultrafine powder. The present invention can still obtain ultrafine powder by adjusting (for example, slightly increasing) the hydrogen content and still maintain a narrow distribution, thereby meeting the needs of customers.
[0013] Another object of the present invention is to prevent the release of hydrogen from the valve metal block during storage to ensure process safety.
[0014] By adopting the present invention, large-sized valve metal ingots can be completely hydrogenated at one time. During the hydrogenation process, the ingots are broken into blocks. The hydrogen embrittlement of the hydrogenated blocks can be controlled within a reasonable range that is conducive to reducing the proportion of ultrafine powder, and the hydrogenated valve metal blocks can be used to produce valve metal powders with narrow particle size distribution and a small ultrafine powder proportion. The valve metal powder produced by the present invention has a small proportion of ultrafine powder, which is conducive to optimizing the performance of the valve metal powder; the present invention uses large-sized valve metal ingots as raw materials, and can effectively control the particle size distribution of the valve metal powder after crushing, which can effectively reduce costs.
[0015] After extensive research, the inventors discovered that the appropriate hydrogen embrittlement of valve metal has an important influence on narrowing the particle size distribution in the crushing and pulverizing process. Too good or too poor hydrogen embrittlement can easily produce ultrafine powder, which is not conducive to the control of particle size distribution in the crushing and pulverizing process.
[0016] The percentages % mentioned herein are by weight unless otherwise stated.
[0017] Accordingly, on the one hand, the present invention provides a valve metal block, and uses the hydrogenated block to crush and powder. If the block is niobium, the hydrogen content is 0.8-1.3%, preferably 0.9-1.2%, and more preferably 0.95-1.1%. The applicant unexpectedly found that if the hydrogen content is too low, below 0.8%, the block does not have hydrogen embrittlement or has poor hydrogen embrittlement, and it is difficult to powderize, and the crushing can only be over-enhanced, resulting in more ultrafine powder; if the hydrogen content is too high, above 1.3%, the hydrogen embrittlement is too good, and the proportion of ultrafine powder after crushing also increases. If the hydrogenated block is tantalum, the hydrogen content is 0.3-0.5%, preferably 0.35-0.45%. If the hydrogen content is too low, below 0.3%, it does not have hydrogen embrittlement or has poor hydrogen embrittlement, and it is difficult to powderize, and the crushing can only be over-enhanced, resulting in more ultrafine powder; if the hydrogen content is too high, above 0.5%, the hydrogen embrittlement is too good, and the proportion of ultrafine powder after crushing also increases.
[0018] On the other hand, the present invention provides a method for manufacturing low-hydrogenated blocks using large-sized valve metal ingots, and the blocks obtained thereby. The method is characterized in that ultra-high purity hydrogen with a dew point below -70°C is used for hydrogenation, preferably ultra-high purity hydrogen with a dew point below -74°C (more preferably, the dew point is below -75°C, and further preferably, the dew point is below -76°C). The use of such hydrogen can reduce the amount of oxygen and other gas impurities in the hydrogenation container caused by the introduction of water and the like by hydrogen, and prevent the formation of oxide films and the like on the surface of unhydrogenated blocks, which can cause passivation; at the same time, in the process of cooling and absorbing hydrogen by the valve metal, by selecting a suitable temperature system, the hydrogen content of the valve metal after hydrogenation can be optimized and controlled, and then the different hydrogen contents of the valve metal hydrogenated blocks can be used to control hydrogen embrittlement, and the particle size distribution of the valve metal powder can be controlled, so as to achieve the purpose of reducing production costs and optimizing the performance of valve metal products. On the other hand, the present invention provides a method for powdering using the above-mentioned blocks, and the powder obtained thereby.
[0019] The present invention relates to a method for making a hydrogenated valve metal block using a valve metal ingot, comprising the following steps:
[0020] (1) heating a valve metal ingot to a first temperature in a hydrogenation container and performing an activation treatment in a hydrogen reducing atmosphere to obtain an activated block;
[0021] (2) cooling the activated block material to absorb hydrogen;
[0022] (3) When the temperature drops to the second temperature, continue to pass hydrogen while keeping the temperature high so that the valve metal absorbs hydrogen evenly, and then stop passing hydrogen;
[0023] (4) The valve metal obtained above is cooled to room temperature, and then the hydrogenated block is taken out from the hydrogenation container.
[0024] The first temperature in step (1) is generally a high temperature of 600-960°C, preferably 650-900°C, and more preferably 700-850°C. Preferably, after heating to the first temperature, the temperature is kept for a period of time, for example (1-20 hours, preferably 3-15 hours, and more preferably 5-12 hours. The hydrogen used is ultra-high purity hydrogen with a dew point below -70°C. Preferably, the valve metal ingot is a large-sized metal ingot as described above. Of course, those skilled in the art will understand that ordinary small-sized metal ingots are also suitable for the present invention, but they cannot give full play to the advantages of the present invention.
[0025] In step (2), cooling the valve metal to absorb hydrogen is a currently known process.
[0026] Step (3) The inventors have found the preferred second temperature through a lot of experimental work. For example, for niobium, the second temperature is preferably any temperature in the range of 200°C-550°C, preferably any temperature in the range of 250°C-300°C; for example, it can be any temperature in the range of 200°C-450°C, it can be any temperature in the range of 300°C-500°C, it can be any temperature in the range of 350°C-400°C. Most preferably, it is any temperature in the range of 300°C-500°C. For tantalum, the second temperature is preferably any temperature in the range of 100°C-400°C. For example, it can be any temperature in the range of 150°C-300°C; it can be any temperature in the range of 250°C-350°C, it can be any temperature in the range of 200°C-400°C, it can be any temperature in the range of 300°C-400°C. Preferably, it is any temperature in the range of 200°C-300°C. The holding time varies depending on the size of the block loaded into the hydrogenation container. For example, the larger the block, the longer the time required. The holding time in this step is usually 3-40 hours, preferably 15-30 hours, and more preferably 15-25 hours.
[0027] In step 4), after the valve metal absorbs the hydrogen remaining in the reaction vessel in step 3), the temperature is lowered in a hydrogen-free atmosphere, and argon is appropriately introduced during the cooling process to maintain a positive pressure in the reaction vessel. Normal temperature refers to room temperature, which is usually minus 20 degrees Celsius to forty degrees Celsius.
[0028] The present invention also relates to a method for preparing powder (for example, by ball milling) using the above-mentioned block as raw material and the powder obtained thereby.
[0029] There is no requirement for hydrogen pressure in the entire hydrogenation process, and the pressure known in the industry shall prevail. However, the inventor unexpectedly discovered that if the hydrogen pressure is controlled at 1-1.5 MPa, it can well balance the requirements of improving efficiency and controlling safety risks. DETAILED DESCRIPTION
[0030] In order to better illustrate the present invention, the following illustrative examples are provided. These examples are merely illustrative and are not intended to limit the scope of the present invention.
[0031] The sample obtained in Example 1 is referred to as Sample 1, the sample obtained in Example A is referred to as Sample A, and so on.
[0032] Embodiment 1:
[0033] After using compressed air to blow off the surface of a cylindrical niobium ingot with a diameter of 450mm and a weight of 800kg, the ingot was loaded into the hydrogenation container of the hydrogenation furnace, and 100g of sodium blocks were added around the niobium ingot. The temperature was raised to 800℃ and kept warm. Ultra-high purity hydrogen with a dew point of -74.5℃ was introduced and the hydrogen pressure was maintained at 1.48MPa. The temperature was kept warm for 15 hours, and then the temperature was lowered and the hydrogen pressure was maintained at 1.48MPa to allow the niobium ingot to fully absorb hydrogen and react with hydrogen. After the temperature dropped to 550℃, the temperature was stopped and the hydrogen pressure was maintained at 1.48MPa. After keeping warm for 20 hours, the introduction of high-purity hydrogen was stopped, the power was turned off for cooling, and argon was appropriately introduced during the cooling process to maintain a positive pressure in the reaction container. The ingot was taken out of the furnace when the temperature was lower than 30℃. There was no abnormality when the cover of the hydrogenation container was opened. The combustible gas detector was used for detection, and the detector did not alarm, indicating that there was no hydrogen overflow. Finally, a hydrogenated block with fully uniform hydrogen absorption, low hydrogen content but good hydrogen embrittlement is obtained. The hydrogenated block is ball-milled and crushed into niobium powder below 100 mesh. The analysis results of the niobium powder are shown in Table 1.
[0034] Embodiment 2:
[0035] After using compressed air to blow off the surface of a cylindrical niobium ingot with a diameter of 450mm and a weight of 800kg, the ingot was loaded into the hydrogenation container of the hydrogenation furnace, and 100g of sodium blocks were added around the niobium ingot. The temperature was raised to 800℃ and kept warm. Ultra-high purity hydrogen with a dew point of -73.2℃ was introduced and the hydrogen pressure was maintained at 1.45MPa. The temperature was kept warm for 10 hours, and then the temperature was lowered and the hydrogen pressure was maintained at 1.45MPa to allow the niobium ingot to fully absorb hydrogen and react with hydrogen. After the temperature dropped to 400℃, the temperature was stopped and the hydrogen pressure was maintained at 1.45MPa. After keeping warm for 25 hours, the introduction of high-purity hydrogen was stopped, the power was turned off for cooling, and argon was appropriately introduced during the cooling process to maintain a positive pressure in the reaction container. The ingot was taken out of the furnace when the temperature was lower than 30℃. There was no abnormality when the cover of the hydrogenation container was opened. The combustible gas detector was used for detection, and the detector did not alarm, indicating that there was no hydrogen overflow. Finally, a hydrogenated block with fully uniform hydrogen absorption, low hydrogen content but good hydrogen embrittlement is obtained. The hydrogenated block is ball-milled and crushed into niobium powder below 100 mesh. The analysis results of the niobium powder are shown in Table 1.
[0036] Embodiment 3:
[0037] After using compressed air to blow off the surface of a cylindrical niobium ingot with a diameter of 450mm and a weight of 800kg, the ingot was loaded into the hydrogenation container of the hydrogenation furnace, and 100g of sodium blocks were added around the niobium ingot. The temperature was raised to 800℃ and kept warm. Ultra-high purity hydrogen with a dew point of -70.8℃ was introduced and the hydrogen pressure was maintained at 1.45MPa. The temperature was kept warm for 10 hours, and then the temperature was lowered and the hydrogen pressure was maintained at 1.45MPa to allow the niobium ingot to fully absorb hydrogen and react with hydrogen. After the temperature dropped to 350℃, the temperature was stopped and the hydrogen pressure was maintained at 1.45MPa. After keeping warm for 25 hours, the introduction of high-purity hydrogen was stopped, the power was turned off for cooling, and argon was appropriately introduced during the cooling process to maintain a positive pressure in the reaction container. The ingot was taken out of the furnace when the temperature was lower than 30℃. There was no abnormality when the cover of the hydrogenation container was opened. The combustible gas detector was used for detection, and the detector did not alarm, indicating that there was no hydrogen overflow. Finally, a hydrogenated block with fully uniform hydrogen absorption, low hydrogen content but good hydrogen embrittlement is obtained. The hydrogenated block is ball-milled and crushed into niobium powder below 100 mesh. The analysis results of the niobium powder are shown in Table 1.
[0038] Example 4 (Comparative Example): After using compressed air to blow off the surface of a cylindrical niobium ingot with a diameter of 450 mm and a weight of 800 kg, the ingot was placed in the hydrogenation container of the hydrogenation furnace, and 100g of sodium blocks were added around the niobium ingot. The temperature was raised to 800°C for insulation, and high-purity hydrogen with a dew point of -64.8°C was introduced and the hydrogen pressure was kept at 1.45MPa. The temperature was kept for 10 hours, and then the temperature was lowered and the hydrogen pressure was kept at 1.45MPa, so that the niobium ingot could fully absorb hydrogen and react with hydrogen. After the temperature dropped to below 30°C, the hydrogen was stopped and the gas in the hydrogenation container was evacuated and replaced twice with argon. When the lid of the hydrogenation container was opened, a blue flame appeared, and hydrogen combustion occurred, which extinguished naturally after about 2 minutes. After the material was taken out of the reaction container, it was found that there were unhydrogenated blocks. The hydrogenated blocks were ball-milled and crushed into niobium powder below 100 mesh. The analysis results of the niobium powder are shown in Table 1.
[0039] Embodiment 5:
[0040] After using compressed air to blow off the surface of a cylindrical niobium ingot with a diameter of 450mm and a weight of 800kg, the ingot was loaded into the hydrogenation container of the hydrogenation furnace, and 100g of sodium blocks were added around the niobium ingot. The temperature was raised to 800℃ and kept warm. Ultra-high purity hydrogen with a dew point of -74.2℃ was introduced and the hydrogen pressure was maintained at 1.45MPa. The temperature was kept warm for 10 hours, and then the temperature was lowered and the hydrogen pressure was maintained at 1.45MPa to allow the niobium ingot to fully absorb hydrogen and react with hydrogen. After the temperature dropped to 200℃, the temperature was stopped and the hydrogen pressure was maintained at 1.45MPa. After keeping warm for 25 hours, the introduction of high-purity hydrogen was stopped, the power was turned off for cooling, and argon was appropriately introduced during the cooling process to maintain a positive pressure in the reaction container. The ingot was taken out of the furnace when the temperature was lower than 30℃. There was no abnormality when the cover of the hydrogenation container was opened. The combustible gas detector was used for detection, and the detector did not alarm, indicating that there was no hydrogen overflow. Finally, a hydrogenated block with fully uniform hydrogen absorption, low hydrogen content but good hydrogen embrittlement is obtained. The hydrogenated block is ball-milled and crushed into niobium powder below 325 mesh. The analysis results of the niobium powder are shown in Table 2.
[0041] Embodiment 6 (comparative example):
[0042] After using compressed air to blow off the surface of a cylindrical niobium ingot with a diameter of 450mm and a weight of 800kg, it was loaded into the hydrogenation container of the hydrogenation furnace, and 100g of sodium blocks were added around the niobium ingot. The temperature was raised to 800℃ and kept warm. High-purity hydrogen with a dew point of -67.2℃ was introduced and the hydrogen pressure was kept at 1.45MPa. The temperature was kept warm for 10 hours, and then the temperature was lowered and the hydrogen pressure was kept at 1.45MPa, so that the niobium ingot could fully absorb hydrogen and react with hydrogen. After the temperature dropped to 50℃, the hydrogen was stopped and the gas in the hydrogenation container was evacuated and replaced twice with argon. When the temperature was lower than 30℃, it was taken out of the furnace. When the cover of the hydrogenation container was opened, it was detected with a combustible gas detector. The detector alarmed and showed that hydrogen overflowed. The alarm was eliminated after about 5 minutes. After the material was taken out of the reaction container, it was found that there were unhydrogenated blocks. The hydrogenated blocks were ball-milled and crushed into niobium powder below 325 mesh. The analysis results of niobium powder are shown in Table 1.
[0043] Table 1 Niobium powder properties
[0044]
[0045] Embodiment A:
[0046] After the surface of a cylindrical tantalum ingot with a diameter of 280mm and a weight of 750kg was blown off and the oxide layer was removed, it was placed in the hydrogenation container of the hydrogenation furnace, heated to 800℃ and kept warm, and ultra-high purity hydrogen with a dew point of -73.0℃ was introduced and the hydrogen pressure was maintained at 1.45MPa. It was kept warm for 15 hours, then cooled and the hydrogen pressure was maintained at 1.45MPa to allow the tantalum ingot to fully absorb hydrogen and react with hydrogen. After the temperature dropped to 400℃, the cooling was stopped and the hydrogen pressure was maintained at 1.45MPa. After keeping warm for 22 hours, the introduction of high-purity hydrogen was stopped, the power was turned off for cooling, and argon was appropriately introduced during the cooling process to maintain a positive pressure in the reaction container. It was taken out of the furnace when the temperature was lower than 30℃. There was no abnormality when the cover of the hydrogenation container was opened. It was detected with a combustible gas detector, and the detector did not alarm, indicating that there was no hydrogen overflow. Finally, a hydrogenated block with fully and uniform hydrogen absorption, low hydrogen content but good hydrogen embrittlement is obtained. The hydrogenated block is ball-milled and crushed into tantalum powder below 100 mesh. The analysis results of the tantalum powder are shown in Table 2.
[0047] Embodiment B:
[0048] After the surface of a cylindrical tantalum ingot with a diameter of 280mm and a weight of 750kg was blown to remove the oxide layer, it was placed in the hydrogenation container of the hydrogenation furnace, heated to 800℃ and kept warm, and ultra-high purity hydrogen with a dew point of -74.5℃ was introduced and the hydrogen pressure was maintained at 1.25MPa. It was kept warm for 10 hours, then the temperature was reduced and the hydrogen pressure was maintained at 1.25MPa to allow the tantalum ingot to fully absorb hydrogen and react with hydrogen. After the temperature dropped to 300℃, the temperature was stopped and the hydrogen pressure was maintained at 1.25MPa. After keeping warm for 25 hours, the introduction of high-purity hydrogen was stopped, the power was turned off for cooling, and argon was appropriately introduced during the cooling process to maintain a positive pressure in the reaction container. It was taken out of the furnace when the temperature was lower than 30℃. There was no abnormality when the cover of the hydrogenation container was opened. It was detected with a combustible gas detector, and the detector did not alarm, indicating that there was no hydrogen overflow. Finally, a hydrogenated block with fully and uniform hydrogen absorption, low hydrogen content but good hydrogen embrittlement is obtained. The hydrogenated block is ball-milled and crushed into tantalum powder below 100 mesh. The analysis results of the tantalum powder are shown in Table 2.
[0049] Example C:
[0050] After the surface of a cylindrical tantalum ingot with a diameter of 280mm and a weight of 750kg was blown off and the oxide layer was removed, it was placed in the hydrogenation container of the hydrogenation furnace, heated to 800℃ and kept warm, and ultra-high purity hydrogen with a dew point of -72.6℃ was introduced and the hydrogen pressure was maintained at 1.15MPa. It was kept warm for 15 hours, then cooled and the hydrogen pressure was maintained at 1.15MPa to allow the tantalum ingot to fully absorb hydrogen and react with hydrogen. After the temperature dropped to 200℃, the cooling was stopped and the hydrogen pressure was maintained at 1.15MPa. After keeping warm for 20 hours, the introduction of high-purity hydrogen was stopped, the power was turned off for cooling, and argon was appropriately introduced during the cooling process to maintain a positive pressure in the reaction container. It was taken out of the furnace when the temperature was lower than 30℃. There was no abnormality when the cover of the hydrogenation container was opened. It was detected with a combustible gas detector, and the detector did not alarm, indicating that there was no hydrogen overflow. Finally, a hydrogenated block with fully and uniform hydrogen absorption, low hydrogen content but good hydrogen embrittlement is obtained. The hydrogenated block is ball-milled and crushed into tantalum powder below 100 mesh. The analysis results of the tantalum powder are shown in Table 2.
[0051] Embodiment D (comparative example):
[0052] After the surface of a cylindrical tantalum ingot with a diameter of 280mm and a weight of 750kg was blown and the oxide layer was removed, it was placed in the hydrogenation container of the hydrogenation furnace, heated to 800℃ and kept warm, and high-purity hydrogen with a dew point of -69.2℃ was introduced and the hydrogen pressure was kept at 1.45MPa. It was kept warm for 15 hours, and then cooled and the hydrogen pressure was kept at 1.45MPa, so that the tantalum ingot can fully absorb hydrogen and react with hydrogen. After the temperature dropped to 30℃, the hydrogen was stopped and the gas in the hydrogenation container was evacuated and replaced twice with argon. When the lid of the hydrogenation container was opened, a blue flame appeared and hydrogen combustion occurred, which went out naturally after about 2 minutes. After the material was taken out of the reaction container, it was found that there were unhydrogenated blocks. The hydrogenated blocks were ball-milled and crushed into tantalum powder below 100 mesh. The analysis results of tantalum powder are shown in Table 2.
[0053] Embodiment E:
[0054] After the surface of a cylindrical tantalum ingot with a diameter of 280mm and a weight of 750kg was blown off and the oxide layer was removed, it was placed in the hydrogenation container of the hydrogenation furnace, heated to 800℃ and kept warm, and ultra-high purity hydrogen with a dew point of -74.7℃ was introduced and the hydrogen pressure was maintained at 1.45MPa. It was kept warm for 15 hours, then the temperature was reduced and the hydrogen pressure was maintained at 1.45MPa to allow the tantalum ingot to fully absorb hydrogen and react with hydrogen. After the temperature dropped to 120℃, the temperature was stopped and the hydrogen pressure was maintained at 1.45MPa. After keeping warm for 25 hours, the introduction of high-purity hydrogen was stopped, the power was turned off for cooling, and argon was appropriately introduced during the cooling process to maintain a positive pressure in the reaction container. It was taken out of the furnace when the temperature was lower than 30℃. There was no abnormality when the cover of the hydrogenation container was opened. It was detected with a combustible gas detector, and the detector did not alarm, indicating that there was no hydrogen overflow. Finally, a hydrogenated block with fully and uniform hydrogen absorption, low hydrogen content but good hydrogen embrittlement is obtained. The hydrogenated block is ball-milled and crushed into tantalum powder below 325 mesh. The analysis results of the tantalum powder are shown in Table 2.
[0055] Example F (Comparative Example):
[0056] After the surface of a cylindrical tantalum ingot with a diameter of 280mm and a weight of 750kg was blown and the oxide layer was removed, it was placed in the hydrogenation container of the hydrogenation furnace, heated to 800℃ and kept warm, and high-purity hydrogen with a dew point of -67.2℃ was introduced and the hydrogen pressure was kept at 1.45MPa. It was kept warm for 15 hours, and then cooled and the hydrogen pressure was kept at 1.45MPa, so that the tantalum ingot can fully absorb hydrogen and react with hydrogen. After the temperature dropped to 50℃, the hydrogen was stopped and the gas in the hydrogenation container was evacuated and replaced twice with argon. When the temperature was lower than 30℃, it was taken out of the furnace. When the cover of the hydrogenation container was opened, it was detected with a combustible gas detector. The detector alarmed and showed that hydrogen overflowed. The alarm was eliminated after about 5 minutes. After the material was taken out of the reaction container, it was found that there were unhydrogenated blocks. The hydrogenated blocks were ball-milled and crushed into tantalum powder below 325 mesh. The analysis results of tantalum powder are shown in Table 2.
[0057] Table 2 Tantalum powder properties
[0058]
[0059] It can be seen that the method of the present invention can reduce the powder size distribution after valve metal hydrogenation crushing and pulverization, reduce the generation of ultrafine powder, thereby reducing the raw material unit consumption in the metal valve metal powder production process, reducing the adverse effects of product fine powder, and optimizing product performance. Moreover, it can achieve one-time hydrogenation of large-scale valve metal ingots, greatly improve production efficiency, effectively reduce production costs, and it is not easy to release low-temperature hydrogen during its processing, storage and transportation, and the safety risk is reduced.
Claims
1. A method for preparing hydrogenated valve metal powder using a valve metal ingot, comprising the following steps: (1) heating a valve metal ingot to a first temperature in a hydrogenation container and performing an activation treatment in a hydrogen reducing atmosphere to obtain an activated block, wherein the hydrogen has a dew point of less than -70°C, and the valve metal ingot weighs more than 100 kg; (2) Cooling the activated block material to absorb hydrogen; (3) When the temperature drops to the second temperature, continue to pass hydrogen while keeping the temperature high so that the valve metal absorbs hydrogen evenly, and then stop passing hydrogen; (4) Cooling the valve metal obtained above to room temperature in a hydrogen-free atmosphere, and then taking out the hydrogenated block from the hydrogenation container. (5) Powdering the valve metal block and crushing it to less than 100 mesh, the -500 mesh powder of the obtained valve metal powder is less than 20%, Wherein when the valve metal is niobium, the hydrogen content of the hydrogenated block is 0.8 to 1.3%, When the valve metal is tantalum, the hydrogen content of the hydrogenated block is 0.3 to 0.5%.
2. The method of claim 1, wherein the first temperature is 600 to 960°C. The method of claim 1 , wherein the first temperature is 650 to 900° C. . The method of claim 1 , wherein the first temperature is 700 to 850° C. .
5. The method according to any one of claims 1 to 4, wherein when the valve metal is tantalum, the hydrogen content of the hydrogenated block is 0.35 to 0.45%.
6. The method according to claim 1, wherein the hydrogen in step (1) has a dew point lower than -75°C.
7. The method according to claim 1, wherein the hydrogen in step (1) has a dew point lower than -76°C.
8. The method according to any one of claims 1 to 7, wherein the insulation time in step (3) is 3 to 40 hours.
9. The method according to any one of claims 1 to 7, wherein the insulation time in step (3) is 4 to 30 hours.
10. The method according to any one of claims 1 to 7, wherein the insulation time in step (3) is 5 to 20 hours.
11. The method according to any one of claims 1 to 10, wherein the valve metal ingot in step (1) weighs more than 200 kg.
12. The method according to any one of claims 1 to 10, wherein the valve metal ingot in step (1) is 300 kg or more.
13. The method according to any one of claims 1 to 10, wherein the valve metal ingot in step (1) weighs 400 kg or more.
14. The method according to any one of claims 1 to 10, wherein the valve metal ingot in step (1) weighs 500 kg or more.
15. The method according to any one of claims 1 to 10, wherein the valve metal ingot in step (1) weighs 600 kg or more.
16. The method according to any one of claims 1 to 10, wherein the valve metal ingot in step (1) weighs 700 kg or more.
17. The method according to any one of claims 1 to 10, wherein the valve metal ingot in step (1) weighs 800 kg or more.
18. A method as claimed in any one of claims 1 to 17, wherein the valve metal ingot in step (1) is less than 1500 kg.
19. The method of any one of claims 1 to 17, wherein the valve metal ingot in step (1) is less than 1400 kg.
20. The method of any one of claims 1 to 17, wherein the valve metal ingot in step (1) is less than 1300 kg.
21. The method of any one of claims 1 to 17, wherein the valve metal ingot in step (1) is less than 1200 kg.
22. The method of any one of claims 1 to 17, wherein the valve metal ingot in step (1) is less than 1100 kg.
23. The method of any one of claims 1 to 17, wherein the valve metal ingot in step (1) is less than 1000 kg.
24. The method according to any one of claims 1 to 23, wherein the -500 mesh powder of the valve metal powder obtained in step (5) is less than 15%.
25. The method according to any one of claims 1 to 23, wherein the -500 mesh powder of the valve metal powder obtained in step (5) is less than 10%.
26. The method according to any one of claims 1 to 23, wherein the -500 mesh powder of the valve metal powder obtained in step (5) is less than 8%.
27. The method according to any one of claims 1 to 23, wherein the -500 mesh powder of the valve metal powder obtained in step (5) is less than 6%.
28. The method of any one of claims 1 to 27, wherein the valve metal is niobium and the second temperature is any temperature in the range of 200°C to 550°C.
29. The method of any one of claims 1 to 27, wherein the valve metal is niobium and the second temperature is any temperature in the range of 250°C to 300°C.
30. The method of any one of claims 1 to 27, wherein the valve metal is niobium and the second temperature is any temperature in the range of 200°C to 450°C.
31. The method of any one of claims 1 to 27, wherein the valve metal is niobium and the second temperature is any temperature in the range of 300°C to 500°C.
32. The method of any one of claims 1 to 27, wherein the valve metal is niobium and the second temperature is any temperature in the range of 350°C to 400°C.
33. The method of any one of claims 1 to 27, wherein the valve metal is niobium and the second temperature is any temperature in the range of 300°C to 500°C.
34. A method as claimed in any one of claims 1 to 33, wherein the valve metal is niobium and the hydrogen content of the hydrogenated mass is from 0.9 to 1.2%.
35. A method as claimed in any one of claims 1 to 33, wherein the valve metal is niobium and the hydrogen content of the hydrogenated mass is from 0.95 to 1.1%.
36. The method according to any one of claims 1 to 35, wherein the pulverizing is carried out by ball milling in step (5).
Citation Information
Patent Citations
Powder metallurgy tantalum powder and / or niobium powder and preparing method thereof
CN103600086A
Production of high-voltage high specific capacitance tantalum powder by means of carbon reduction
CN1035852A